Tailoring the hybrid palliation for hypoplastic left heart syndrome: A simulation study using a lumped parameter model. Issue 9 (September 2015) - Di Molfetta, A.; Pilati, M.; Gagliardi, M.G.; Fresiello, L.; Amodeo, A.; Cristofaletti, A.; Pongiglione, G.; Ferrari, G.
Highlights: Lumped parameter models could be useful to support clinical decision in complex heart diseases such as hypoplastic left heart syndrome. Lumped parameter models could be useful in calibrating and tailoring the hybrid palliation procedure. Lumped parameter models could support the setting the parameters that play a role on flow distribution in hybrid palliation such as patent ductus arteriosus stent size, atrial septal defect size, pulmonary artery banding tightness, the necessity of a reverse Blalock–Taussig shunt. Abstract: The results of Hybrid procedure (HP) for the hypoplastic left heart syndrome (HLHS) depend on several variables: pulmonary artery banding tightness (PAB), atrial septal defect size (ASD) and patent ductus arteriosus stent size (PDA). A HP complication could be the aortic coarctaction (CoAo). The reverse Blalock–Taussig shunt (RevBT) placement was proposed to avoid CoAo effects. This work aims at developing a lumped parameter model (LPM) to investigate the effects of the different variables on HP haemodynamics. A preliminary verification was performed collecting measurements on a newborn HLHS patient to calculate LPM input parameters to reproduce patient's baseline. Results suggest that haemodynamics is affected by ASD (ASD: 0.15–0.55 cm, pulmonary to systemic flow ratio Q  p / Q  s : 0.73–1, cardiac output (CO): 1–1.5 l/min and ventricular stroke work SW: 336–577 ml mmHg) and by the PAB diameter (PAB: 0.07–0.2 cm, Q  p / Q  s : 0.46–2.1, CO: 1.3–1.6 l/min and SW: 591–535 ml mmHg). Haemodynamics was neither affected by RevBT diameter nor by PDA diameter higher than 0.2 cm. RevBT implantation does not change the HP haemodynamics, but it can make the CoAo effect negligible. LPM could be useful to support clinical decision in complex physiopathology and to calibrate and personalise the parameters that play a role on flow distribution.